The elements of political communication on Facebook - Tasente, Tanase (Technium Social Sciences Journal, 2021)
In its role as a tool that facilitates participation, Facebook acts as a channel of political communication with different mechanisms than traditional media. At the same time, Facebook offers new means of receiving the audience, characterized by a targeting of the very good target audience. The Facebook page of a political party facilitates interaction and political participation, making possible a two-way communication model and facilitating increased political participation of public opinion. The platform is not mediated and has no boundaries as traditional media has, which means that parties have direct access to more people than ever. Moreover, it is also noted that, on Facebook, the political message does not go through the editorial policy filters as it happens in traditional media and is used as a powerful interaction tool with the target audience or even with a public not ever considered by the political communication strategies.